Transplantation of glial cells enhances action potential conduction of amyelinated spinal cord axons in the myelin-deficient rat. - Utzschneider, D A (1994)
A central issue in transplantation research is to determine how and when transplantation of neural tissue can influence the development and function of the mammalian central nervous system. Of particular interest is whether electrophysiological function in the traumatized or diseased mammalian central nervous system can be improved by the replacement of cellular elements that are missing or damaged. Although it is known that transplantation of neural tissue can lead to functional improvement in models of neurological disease characterized by neuronal loss, less is known about results of transplantation in disorders of myelin. We report here that transplantation of glial cells into the dorsal columns of neonatal myelin-deficient rat spinal cords leads to myelination and a 3-fold increase in conduction velocity. We also show that impulses can propagate into and out of the transplant region and that axons myelinated by transplanted cells do not have impaired frequency-response properties. These results demonstrate that myelination following central nervous system glial cell transplantation enhances action potential conduction in myelin-deficient axons, with conduction velocity approaching normal values.